Classification of MANET routing protocols - Tepšić, Dejan M.; Veinović, Mladen Đ. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Mobile ad hoc networks (MANETs) are self-configuring networks of nodes connected via wireless without any form of centralized administration. This kind of networks is currently one of the most important research subjects due to a huge variety of applications (military, emergency, etc.). In MANETs, each node acts both as a host and as a router, thus it must be capable of forwarding packets to other nodes. Because of the node mobility, topologies of these networks change frequently. Traditional routing protocols used in wired networks cannot work efficiently in MANETs. Therefore, special routing protocols for MANETs are needed. The objective of this paper is to research the current state of the art of existing routing protocols for MANETs, and to compare different approaches. Routing protocols are classified according to the method of forwarding packets into unicast, multicast and broadcast. There are three main classes of unicast routing protocols for MANETs: proactive, reactive and hybrid. Introduction A mobile ad hoc network (MANET) is a dynamic network that allows wireless networking on the go, without the need for pre-built network infrastructure. It consists of mobile nodes, where a node can be a man carrying a handheld computer equipped with appropriate devices for wireless communications, a laptop computer, a robot, or anyone who is equipped with the appropriate equipment for wireless communication. MANET networks operate without centralized infrastructure, while the nodes mutually cooperate to ensure connectivity. MANET routing protocols When establishing communication over the wireless network, if two nodes are not directly connected through a communication link, messages must be forwarded through transit nodes. Finding the routes between two nodes that send messages within the communication network is called routing. Routing protocols designed for use in traditional fixed networks cannot be used in MANET networks. The specific characteristics of these networks require special routing protocols that deal with solving the specific challenges. Classification of the existing MANET routing protocols Unicast routing protocols designed for use in mobile ad hoc wireless networks can be classified according to the mechanism of updating information on routes into three categories: - proactive (periodic) routing protocols - each node maintains one or more tables in order to preserve the network topology and the information about the routes, - reactive (on-demand) routing protocols - routes are found only when needed, - hybrid routing protocols - combines features of proactive and reactive routing protocol. Multicast routing protocols Multicast routing protocols can be classified into four categories according to the route construction method: tree based, mesh based, hybrid, and stateless routing protocols. Broadcast routing protocols Broadcast routing protocols can be classified into the following categories: counter-based, area-based, neighbor-based, cluster-based and probabilistic-based methods. The choice of unicast routing protocol in MANETs When it comes to choosing a unicast routing protocol within the MANET network, the reactive approach achieves better results when node mobility is high and when the amount of traffic transmitted between the nodes is small. On the other hand, proactive routing protocols are recommended when the network is generally static, and when the amount of generated traffic between nodes is high. When a balance between the different models of the mobility of nodes and different amounts of generated traffic between nodes within a network is needed, it is recommended to use a hybrid routing protocol which combines both classes of protocols, a proactive one and a reactive one. Conclusion The topology of mobile ad hoc networks can be dynamic and unpredictable. Traditional routing protocols used in cable networks cannot be directly applied to mobile ad hoc wireless networks. Three major classes of unicast routing protocols are proactive, reactive and hybrid.